Effects of the ketogenic diet on bone health: A systematic review - Garofalo, Vincenzo; Barbagallo, Federica; Cannarella, Rossella; Calogero, Aldo Eugenio; La Vignera, Sandro; Condorelli, Rosita Angela (Frontiers in Endocrinology, 2023)
Objective: To carry out a systematic review of published studies to evaluate the relationship between different type of ketogenic diet (KD) and bone health as supported by the scientific literature. Methods: The study involved all articles that assessed the relationship between the use of KD for the treatment of overweight or obesity and bone health. The quality assessment was evaluated with using the Cambridge Quality Checklists. The search strategy included the following combination of Medical Subjects Headings terms and keywords: "osteoporosis", "bone health, "bone function", "bone mineral density", and "ketogenic diet". Results: Seven trials were identified and reviewed. No significant changes in bone mass density (BMD) were observed after KD. The results showed no significant effect on bone resorption by measuring urinary N-telopeptide levels, on bone formation by measuring bone-specific alkaline phosphatase, or alterations in overall bone turnover in patients who followed KD. Only in female subject after a 10% weight loss, bone resorption increases while new bone synthesis decreases, but without increasing the risk of osteoporosis. Finally, patients on KD lost significantly more weight than controls, associated with an increase in serum vitamin D levels and a reduction in plasma parathyroid hormone (PTH) levels. Conclusion: No human studies have currently been conducted with adequate and powerful experimental designs to definitively understand the impact of KD therapy on bone health.